Recent Advances in Porcine Reproductive and Respiratory Syndrome Virus NADC30-Like Research in China: Molecular Characterization, Pathogenicity, and Control - Yu, Ying; Zhang, Qiaoya; Cao, Zhi; Tang, Yan-Dong; Xia, Dasong; Wang, Gang; Shan, Hu (Frontiers in Microbiology, 2022)
The name PRRSV (porcine reproductive and respiratory syndrome virus) NADC30-like was first coined in 2015, which originated from the NADC30 strain that was introduced into China by importing of breeding pigs and has since undergone mutations or recombination, resulting in variant viruses. Following widespread outbreaks in China in recent years, these NADC30-like strains have presented major health challenges in swine production systems. Outcomes induced by PRRSV NADC30-like infection are highly variable, ranging from inapparent to severe, depending on the recombination between NADC30 and field PRRSV strains prevalent in swine farms. Vaccines and strict biosecurity measures have been explored to fight against this disease; however, current PRRSV commercially modified-live virus vaccines (MLVs) have the potential to revert to virulence and only provide limited or no cross-protection efficacy against NADC30-like strains. PRRSVs will remain an ongoing challenge to the swine industry until safe and effective vaccines or antiviral reagents are development.